2017
DOI: 10.1016/j.jstrokecerebrovasdis.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Interventions Reduce Time-to-Thrombolysis for Acute Ischemic Stroke in a Public Safety Net Hospital

Abstract: Background and Purpose: Shorter time-to-thrombolysis in acute ischemic stroke (AIS)is associated with improved functional outcome and reduced morbidity. We evaluate the effect of several interventions to reduce time-to-thrombolysis at an urban, public safety net hospital. Methods: All patients treated with tissue plasminogen activator for AIS at our institution between 2008 and 2015 were included in a retrospective analysis of door-to-needle (DTN) time and associated factors. Between 2011 and 2014, we implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Stroke pharmacists were trained and equipped with a mobile clot box containing labetalol, tPA and other equipment to facilitate tPA preparation and administration in the CT suite, expediting timely reperfusion therapy delivery. 15 The results were similarly replicated in two retrospective cohort studies which found the involvement of an ED stroke pharmacist is independently associated with a DNT reduction of up to 23 minutes. 14,54 The retrospective nature of the studies and different times of ED presentation in the patient groups introduces chronology bias and may skew workflow benefits in favour of the pharmacy group.…”
Section: Imaging To Intravenous Thrombolysismentioning
confidence: 62%
See 2 more Smart Citations
“…Stroke pharmacists were trained and equipped with a mobile clot box containing labetalol, tPA and other equipment to facilitate tPA preparation and administration in the CT suite, expediting timely reperfusion therapy delivery. 15 The results were similarly replicated in two retrospective cohort studies which found the involvement of an ED stroke pharmacist is independently associated with a DNT reduction of up to 23 minutes. 14,54 The retrospective nature of the studies and different times of ED presentation in the patient groups introduces chronology bias and may skew workflow benefits in favour of the pharmacy group.…”
Section: Imaging To Intravenous Thrombolysismentioning
confidence: 62%
“…Interventions prior to the administration of reperfusion therapy include ambulance prenotification, direct patient transportation to imaging, tele‐stroke consultation and point‐of‐care testing (POCT) 10‐13 . The use of stroke pharmacists, bedside preparation and administration of thrombolytic therapy has been proposed to streamline reperfusion therapy delivery 14,15 . The utility of direct‐to‐angiography transport and parallel, standardized workflow has similarly been indicated to streamline thrombectomy procedures 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, diagnosis can be established through bedside examination by specialists because it is a qualitative measurement. If the symptom occurs outside a hospital, a substantial time delay can cause poor outcomes for acute stroke patients [ 3 - 5 ]. In addition, the objective and accurate neurological assessments are not possible by mere visual examination because the examiner cannot easily trace the movement using the conventional neurological examination when there are subtle weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…The role of care delivery by safety-net hospitals has been examined in other neurologic disease states including thrombolysis for stroke and radiosurgery for metastatic brain cancer. [23, 24] However, impact of hospital safety-net burden on endovascular treatment of ruptured brain aneurysms remains unstudied. This investigation aims to determine the impact of hospital safety net status on time to endovascular treatment of ruptured brain aneurysms.…”
Section: Introductionmentioning
confidence: 99%